Spatial Evolution of the Effects of Urban Heat Island on Residents' Health - Huanchun Huang (Tehnički Vjesnik, 2020)
Rising summer temperatures caused by the urban heat island (UHI) has considerable effects on the physical and mental health of urban residents globally. To categorize residents’ health risk areas and evaluate the characteristics of urban spatial evolution, based on data analysis methods, such as ArcGIS, ENVI software, and geostatistical analysis, data from meteorological stations, satellite images, and electronic maps were used to investigate spatial evolution and the process by which UHI affects the respiratory, circulatory, and cardiovascular systems and emotional health of the residents of Tianjin. Results show the UHI significantly increases respiratory, circulatory, and cardiovascular diseases. The emotional health of residents is also significantly affected with the affected level moving from level 1 to level 2-4. Highly concentrated areas in the urban center and patches with high health risks are found to be scattered and fragmented, as indicated by the phased pattern of spatially deteriorating hotspots. Hotspots expansion occurs unidirectionally to the south, surrounding the city center, while shrinking from the inside to the outside. The study identifies urban health space risks and provides theoretical guidance for urban space optimization and healthy urban planning.